Composts use to improve fertility of a slope Luvisol soil - Hernández de la Cruz, Osvaldo Baldemar; Sánchez Hernández, Rufo; Ordaz Chaparro, Víctor Manuel; López Noverola, Ulises; Estrada Botello, Maximiano Antonio; Pérez Méndez, Miguel Angel (Revista Mexicana de Ciencias Agrícolas, 2017)
The aim of this research was to determine the changes in the physical and chemical properties due to the use of 0, 20, 40 and 60 Mg ha-1 compost in a chromic slope Luvisol in humid tropical conditions. A completely randomized block experiment with four replicates was established. The results indicate that doses higher than 40 Mg ha-1 of compost increase the porosity and hydraulic conductivity, reduce the bulk density and penetration resistance in the surface layer (-10 cm). The size and stability of the aggregates are reduced according to the increase in the compost dose, which is interpreted as an intermediate stage, of a rapid aggregation-disaggregation-aggregation process. The contribution over 40 Mg ha-1 of the organic amendment modified levels of organic matter, cation exchange capacity and percent base saturation, only slight increases were observed in K, Ca, Mg, Fe and Zn, and no changes were observed in pH.